Rede de sensores resistivos para monitoração de escoamento bifásico em longas distâncias - Dias, Rafael Bressan (2015)
Liquid-gas two-phase flows are present in many industrial applications, such as in oil exploration and production, where normally such flows are confined to pipes. Flow monitoring in pilot plants and in controlled conditions is of great importance for a better understanding of physical phenomena, which in turn are employed for validation and improvement of flow models. Measuring parameters along the pipe is often required to observe the evolution of the flow. In this work, the design and construction of a measuring system comprising of resistive sensors interconnected to a CAN (controller area network) bus, enabling flow monitoring at distances of up to tens of meters. The system is based on previous works at UTFPR and expands the flow the capacity of Research Center of Multiphase Flows (NUEM) at UTFPR. Both sensors and data acquisition electronics as well as the firmware of the microcontroller involved and the system supervision software have been developed. After some static tests, the system was tested in flowing conditions in a pilot-plant, showing good performance. Hence being a appropriate new tool for monitoring liquid-gas two-phase flows.